2019
DOI: 10.1002/alr.22355
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of computed tomography in the recurrence of chronic rhinosinusitis with nasal polyps

Abstract: Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is a nasal disease with a high tendency for recurrence. The aim of this study was to compare the use of computed tomography (CT) scan with other clinical parameters in predicting the recurrence of CRSwNP. Methods A total of 272 consecutive CRSwNP patients undergoing endoscopic functional sinus surgery were recruited. The demographic characteristics and clinical parameters, including CT scores, level of exhaled nitric oxide, and peripheral eosinophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…In addition, we found that E/M ratio differed significantly between the two endotypes and was associated with nNO for Eos CRSwNP patients suggesting Lund–Mackay score may play a coincidental role, rather than an E/M role in endotypes of CRSwNP. The findings of the present study were partially in accordance with the findings of Mend [ 9 ]. Similarly, Ishitoya indicated that CT scans of Eos CRSwNP patients typically show “ethmoid sinusdominant opacification,” with opacification of the olfactory cleft also being a feature [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, we found that E/M ratio differed significantly between the two endotypes and was associated with nNO for Eos CRSwNP patients suggesting Lund–Mackay score may play a coincidental role, rather than an E/M role in endotypes of CRSwNP. The findings of the present study were partially in accordance with the findings of Mend [ 9 ]. Similarly, Ishitoya indicated that CT scans of Eos CRSwNP patients typically show “ethmoid sinusdominant opacification,” with opacification of the olfactory cleft also being a feature [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, some scholars have proposed that CRSwNP can be divided into two endotypes based on the degree of eosinophil infiltration into the nasal mucosa: eosinophilic CRSwNP (Eos CRSwNP) and non-eosinophilic CRSwNP (Non-Eos CRSwNP) [ 5 ]. Compared with Non-Eos CRSwNP, Eos CRSwNP was shown to be frequently associated with extensive olfactory dysfunction [ 6 ], higher incidence of asthma [ 7 ], greater sensitivity to glucocorticoid therapy [ 8 ], higher recurrence rates, and higher computed tomography (CT) score [ 9 ]. The gold standard for the classification of eosinophilic and non-eosinophilic CRSwNP is histologic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that better surgical interventions or the long-term application of postoperative intranasal GCs may prevent or delay recurrence [7, 9, 13, 57]. To date, novel parameters and biomarkers, in addition to tissue and peripheral blood eosinophil counts and percentages, have been proposed as predictive factors for recurrence and are worth further investigating, including CLC [33, 34, 41, 58-61].…”
Section: Discussionmentioning
confidence: 99%
“…Self-report symptoms were evaluated using a 0–10 point visual analog scale (VAS) system, where 0 indicated the absence of any symptoms and 10 indicated the presence of the most severe symptoms [1]. CT scan findings were evaluated by the Lund-Mackay staging system, where for frontal, sphenoid, maxillary, and anterior and posterior ethmoid sinuses at each side, 0 (no opacification), 1 (partial opacification), and 2 (total opacification) were used; where for ostiomeatal complex at each side, 0 (not occluded) and 2 (occluded) were used, and the E/M ratio of the Lund-Mackay score (0–8) was calculated [39-41]. The size of the polyps in each side of the nasal cavity was measured endoscopically by using the nasal polyp size score (NPSS, 0–4, a higher score representing a larger size of polyps, see online suppl.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in developing predictive markers or models have brought us one step closer toward tailoring treatment more appropriately for a given patient. Meng et al . suggested that a cutoff point of 2.55 for the E/M ratio (the ratio of total ethmoid sinus scores for both sides and maxillary sinus score for both sides) indicated the highest predictive value of CRS with nasal polyps (CRSwNP) recurrence with a sensitivity of 95.8% and a specificity of 91.1%.…”
mentioning
confidence: 99%